The Influence of Education Level and Economic Growth on the Labor Force Participation Rate in Indonesia - Anita Gracia; Josephine Wuri; Yuliana Rini Hardanti; Antonius Budisusila (Green Publisher Indonesia, 2025)
The labor force participation rate plays an important role in addressing unemployment in Indonesia. The labor force participation rate in Indonesia continues to fluctuate annually. Increasing education levels and economic growth are needed to boost the labor force participation rate. This study aims to analyze the effect of education level and economic growth on the participation rate of the labor force in Indonesia. Education levels and economic growth play major roles in boosting the labor force participation rate in Indonesia. The data used in this study consist of annual secondary data for the period 2005–2024 from the Central Statistics Agency (Badan Pusat Statistik, BPS). The analysis tool used is multiple linear regression. The results show that education level has a positive and significant effect on the labor force participation rate, while economic growth does not have a significant effect. The findings suggest important policy implications: governments should prioritize educational development programs to enhance workforce participation, while economic growth strategies should be redesigned to create quality employment opportunities that effectively absorb the labor force. This study contributes to the literature by providing comprehensive empirical evidence on the differential impacts of education and economic growth on labor force participation in Indonesia, highlighting the critical role of human capital development in labor market dynamics. Future research should investigate the moderating effects of other socioeconomic factors and explore sector-specific variations in these relationships.